2022
DOI: 10.1038/s41551-022-00937-8
|View full text |Cite
|
Sign up to set email alerts
|

A soft robotic sleeve mimicking the haemodynamics and biomechanics of left ventricular pressure overload and aortic stenosis

Abstract: Existing models of aortic stenosis (AS) are limited to inducing left ventricular pressure overload. As they have reduced control over the severity of aortic constriction, the clinical relevance of these models is largely hindered by their inability to mimic AS hemodynamics and recapitulate ow patterns associated with congenital valve defects, responsible for the accelerated onset and progression of AS. Here we report the development of a highly tunable bio-inspired soft robotic tool that enables the recapitula… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 63 publications
0
18
0
Order By: Relevance
“…Biomechanical mimicry of the AS lesion is paramount to accurately recreate local flow hemodynamics in a high-fidelity platform. In this work, calculation of the DSC between the model and CT images demonstrated that the patient-specific aortic sleeve can achieve enhanced mimicry (DSC = 0.88 ± 0.05) compared with commercial aortic banding techniques (DSC = 0.47) and nonspecific aortic sleeves (DSC = 0.72) ( 30 ). Furthermore, our platform recapitulates the hemodynamics of AS (Fig.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Biomechanical mimicry of the AS lesion is paramount to accurately recreate local flow hemodynamics in a high-fidelity platform. In this work, calculation of the DSC between the model and CT images demonstrated that the patient-specific aortic sleeve can achieve enhanced mimicry (DSC = 0.88 ± 0.05) compared with commercial aortic banding techniques (DSC = 0.47) and nonspecific aortic sleeves (DSC = 0.72) ( 30 ). Furthermore, our platform recapitulates the hemodynamics of AS (Fig.…”
Section: Discussionmentioning
confidence: 88%
“…The controllability of molding or MM3DP-based hydrodynamic models is further limited by differences between the mechanical properties of the manufactured valve material and those of the native leaflet tissue. Although the investigation of valve kinetics was beyond the scope of this work, the dynamics of the aortic sleeve in this model could be controlled to mimic the motion of stenotic valve leaflets, as previously demonstrated (30). Unlike other models, our platform was also able to recreate the anatomies of congenital valvular defects, such as BAV (patients 12 to 15 in Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Actuators have been widely used in biomedicine and other fields. 33,34 However, in complicated and unknowable environments, identifying the type and size of the object the actuator is in contact with is a huge challenge. Tactile feedback is made possible in uncharted surroundings by combining TDAs with deformability and TENGs that produce various electrical signals when in touch with different materials.…”
Section: Application Of Tda As An Object Identification Sensormentioning
confidence: 99%